Cultural Values in French Textbook for Beginner Learners - Raden Sasnitya; Wawan Gunawan; Budi Hermawan; Ysé Lacroix (Jurnal Ilmu Pendidikan, 2025)
This study examines the representation of French cultural values in the Tendances A1 textbook, which is widely used in Indonesia for teaching French as a Foreign Language (FLE). Adopting a Critical Discourse Analysis (CDA) approach, the research investigates how cultural elements are conveyed both textually and visually through Fairclough’s three-dimensional framework of description, interpretation, and explanation. Using Widodo’s (2018) model of cultural dimensions respect for cultural differences, indigenous cultures, harmony with life and nature, and appreciation for local creativity the study categorizes and analyzes content drawn from dialogues, images, and thematic contexts. Descriptive statistics and qualitative coding show that seven of nine cultural aspects from the unité culture framework are present, including daily life, interpersonal relationships, values and beliefs, living conditions, manners, and rituals. These aspects emerge through scenes of social greetings like La Bise, family dynamics, leisure habits, gift-giving, and home preferences, reflecting both explicit and implicit ideologies. The findings suggest that Tendances A1 successfully integrates linguistic and cultural competence, enabling learners to gain not only language skills but also awareness of French social norms and values; however, the study also notes the need for greater cultural diversity and contextualization to avoid stereotypes. Ultimately, the research underscores the importance of embedding authentic, varied cultural content in language education to promote meaningful, globally conscious communication.